Hubungan Infiltrasi Limfovaskular dengan Subtipe Molekuler Kanker Payudara Invasif : Telaah Sistematis - Yosef Yantamajaya Simbolon (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background: Breast cancer should be found at an earlier stage, but this cancer is more often recognized at an advanced stage which causes high mortality. Poor cancer prognosis will affect the patient's quality of life, financial condition, role and function of the patient and family and even death. The prognosis in breast cancer patients is based on the analysis of primary tumor biological markers which include estrogen receptor (ER), progesterone receptor (PR), Human Epidermal Growth Factor Receptor 2 (HER2) and Ki67 which are classified into 4 molecular subtypes, namely Luminal A, Luminal B, HER2 overexpression, and Triple Negative. Method: This type of research uses a systematic review study method with the data to be used are research results that have been circulating in the world. The population of this study is the journal literature search results regarding lymphovascular infiltration of molecular subtypes of breast cancer published in international journals and accessible via the internet. The research sample was determined based on several inclusion and exclusion criteria that have been made. Results: From 5 international journals that have been collected, then analyzed using a forest plot. Based on the data analysis, it was found that P = 0.21, which means that the subgroup difference test showed that there was no statistically significant subgroup effect. Conclusion: There was no association between lymphovascular infiltration and molecular subtypes of invasive breast cancer